REPORT ON STUDENT QUALITY DEVELOPMENT WITH STUDENT SUPPORT SYSTEM OF WAT KUIBURI SCHOOL - Tuekhwamsat, Chalermkhwan (Journal for Developing the Social and Community, 2023)
Report on student quality development with student support system of wat kuiburi school aimed at 1) study the operating conditions of student quality development with the student support system of wat kuiburi school and 2) Study the results of student quality development with the student support system of Wat Kuiburi School. Population in this study consist of teacher, board of basic education institutions,student parents and students the sample group consisted of teachers, 13 people, board of basic educational institutions, 9 people, parents of 132 students and 132 students academic year 2021 The tool is an estimation scale questionnaire of 4 items. 1) condition questionnaire Implementation of student quality development with student support system of Wat Kuiburi School For teachers and the board of basic education institutions. 2) Student quality questionnaire at Wat Kuiburi School for teachers. 3) Student Quality Questionnaire of Wat Kuiburi School for parents of students. 4) Student quality questionnaire of Wat Kuiburi School for students and 1 interview form For teachers and students' parents about the learner quality of Wat Kuiburi School. The statistics used to analyze the data were frequency (f), mean (), percentage (%), standard deviation (S.D.). The results showed that Operating conditions for student quality development with the student support system of Wat Kuiburi School Overall, the practice was at the highest level. Performance of student quality development with student support system of Wat Kuiburi School As a result, the number of at-risk students and problem groups were reduced. The students had 8 desirable characteristics and life skills according to their 5 key competencies. Overall, the level was at the highlevel.